2013
DOI: 10.1177/0021998313494918
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of multistitched two-dimensional (2D) woven E-glass/polyester composites under low-velocity impact load

Abstract: The aim of this study was to understand the low-velocity impact energy absorption mechanism of the developed two-dimensional multistitched multilayer E-glass/polyester-woven composites. It was found that the specific front and back face damaged areas of the two-dimensional multistitched E-glass/polyester-woven composites were smaller than those of the two-dimensional unstitched structures. When the stitching density increases, the front and back face damaged areas generally decrease. In addition, when the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The tup geometry was circular‐cylindrical, with a 19 mm diameter and a hemispherical nose and the work of tup deformation is neglected. Results of low velocity impact on multi‐stitched composite have been published . Therefore, their data were not discussed in the article to avoid repetition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tup geometry was circular‐cylindrical, with a 19 mm diameter and a hemispherical nose and the work of tup deformation is neglected. Results of low velocity impact on multi‐stitched composite have been published . Therefore, their data were not discussed in the article to avoid repetition.…”
Section: Methodsmentioning
confidence: 99%
“…Stitching improved fracture toughness failure mode‐I behavior, thereby increasing the damage resistance of 2D stitched composites . Stitching directions and density, type of the stitching fiber, and type of stitch influence the mechanical properties of multi‐stitched composites . Several studies showed that densely stitched composites showed higher energy absorption and less damage size than loosely stitched composites .…”
Section: Introductionmentioning
confidence: 99%
“…However, they suffer delamination. To develop a delamination free structure, Z‐directional preforms were developed by three dimensional (3D) weaving , 3D braiding , and stitching which are sewing, tufting, or embroidery . Recently, nanosphere, single wall, or multiwall tubes were employed in fiber composites by dispersing the nano in the resin using various techniques such as shear mixing, ultrasonication, and transfer‐printing .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [16] extensively studied the tension -tension characteristics of 3D multi-axial warp knitted epoxy composites. Bilisik and Yolacan [17] carried out experiments to study the low velocity impact energy absorption mechanism of unstitched and stitched multi-layer plain weave fabrics. The stitching was done using yarns of aramid, E-glass, Carbon and Nylon.…”
Section: Introductionmentioning
confidence: 99%